A Novel Approach to Assessing Professionalism in Preclinical Medical Students Using Multisource Feedback Through Paired Self- and Peer Evaluations. Issue 4 (2nd October 2017) - Emke, Amanda R.; Cheng, Steven; Chen, Ling; Tian, Dajun; Dufault, Carolyn
ABSTRACT: Phenomenon: Professionalism is integral to the role of the physician. Most professionalism assessments in medical training are delayed until clinical rotations where multisource feedback is available. This leaves a gap in student assessment portfolios and potentially delays professional development. Approach: A total of 246 second-year medical students (2013–2015) completed self- and peer assessments of professional behaviors in 2 courses following a series of Team-Based Learning exercises. Correlation and regression analyses were used to examine the alignment or misalignment in the relationship between the 2 types of assessments. Four subgroups were formed based on observed patterns of initial self- and peer assessment alignment or misalignment, and subgroup membership stability over time was assessed. A missing data analysis examined differences between average peer assessment scores as a function of selective nonparticipation. Findings: Spearman correlation demonstrated moderate to strong correlation between self-assessments completed alone (no simultaneous peer assessment) and self-assessments completed at the time of peer assessments (ρ = .59, p < . 0001) but weak correlation between the two self-assessments and peer assessments (alone: ρ = .13, p < . 013; at time of peer: ρ = .21, p < . 0001). Generalized estimating equation models revealed that self-assessments done alone ( p < .0001) were a significant predictor of self-assessments done at the time of peer. Course was also a significant predictor ( p = .01) of self-assessment scores done at the time of peer. Peer assessment score was not a significant predictor. Bhapkar's test revealed subgroup membership based on the relationship between self- and peer ratings was relatively stable across Time 1 and Time 2 assessments (χ 2 = 0.83, p = .84) for all but one subgroup; members of the subgroup with initially high self-assessment and low peer assessment were significantly more likely to move to a new classification at the second measurement. A missing data analysis revealed that students who completed all self-assessments had significantly higher average peer assessment ratings compared to students who completed one or no self-assessments with a difference of –0.32, 95% confidence interval [–0.48, –0.15]. Insights: Multiple measurements of simultaneous self- and peer assessment identified a subgroup of students who consistently rated themselves higher on professionalism attributes relative to the low ratings given by their peers. This subgroup of preclinical students, along with those who elected to not complete self-assessments, may be at risk for professionalism concerns. Use of this multisource feedback tool to measure perceptual stability of professionalism behaviors is a new approach that may assist with early identification of at-risk students during preclinical years.